Locating optimal position of artificial recharge wells in aquifer using grey wolf optimization algorithm and isogeometric numerical method - F. Poursalehi; A. Akbarpour; S. R. Hashemi (Applied Water Science, 2022)
Abstract The construction of injection wells is one of the direct methods of artificial recharge and determining their optimal location is one of the important issues that are discussed in the topics of projects related to the rehabilitation of aquifers. In this research, a simulation–optimization model was proposed to determine the optimal location of injection wells using the Isogeometric analysis (IGA) numerical model and the Grey wolf optimization algorithm (GWO). In this regard, first, a groundwater model based on Isogeometric analysis was created to simulate groundwater flow in a hypothetical aquifer. Finally, after ensuring the accuracy of the simulator model, the optimal location of 10 injection wells was evaluated under two scenarios based on different values of hydraulic conductivity and specific yield. The accuracy of the simulation model is computed based on three error criteria ME, MAE and RMSE were the evaluation criteria which equaled −0.96%, 1.11%, and 0.0146 m, respectively. The achieved results showed that the Isogeometric analysis model has high accuracy. The results of the IGA-GWO model indicated that after constructing injection wells in the optimal location, the groundwater table on average in 10 injection wells rises more than 50 cm in both scenarios. The results also showed that due to the change in aquifer hydraulic conductivity and specific yield in different regions and the defined boundary conditions in the problem, the optimal location of injection wells are in regions with more hydraulic conductivity and more specific yield. Also, injection in regions with more drops will increase the groundwater table.